Pengembangan Wilayah Pantai Pulau Merak Kecil Berbasis Lingkungan, Ekonomi, dan Olahraga (Ecosport Tourism): Development of Pantai Pulau Merak Kecil Based on Environment, Economy, and Sports (Ecosport Tourism) - 'Aqobah, Qory Jumrotul; Nuryadin, Arief; Triprayogo, Rian; Rahayu, Ayu; Anugrah, Sendy Mohamad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Pantai Pulau Merak in Pulomerak District, Cilegon City, Banten, has quite a large coastal tourism potential with natural beauty and charming camping areas. However, the lack of facilities, skilled workers, and financial support are obstacles to its development. To overcome this, a development plan based on ecosport tourism is proposed that combines ecotourism with sports activities as a solution. Ecosport tourism offers a combination of natural beauty with sports, supports environmental conservation, and improves the local economy. This plan includes mapping related sports branches, building sports facilities, and preparing management and promotion systems. The implementation method includes coordination with various partners, field surveys, designing sports venues, and evaluating activities. The expected result is the realization of an international standard area that can improve the local economy and attract tourists. This program will also be disseminated through scientific publications and registration of community service videos to related institutions.